Business Analysis Of Utilizing Lettuce Roots As A Substitute For Rockwool As A Growing Medium In Lettuce (Lactuca Sativa L.) Hydroponic Cultivation Systems - Athallah, Ilham Iqbal; Saikhu, M.; Pratiwi, Arum (Jurnal Multidisiplin Dehasen (MUDE), 2025)
Hydroponics is a solution for urban agriculture with limited land, but the use of the expensive rockwool as a growing medium increases production costs. This study aims to analyze the utilization of lettuce root waste product as an alternative for growing medium in hydroponic lettuce cultivation (Lactuca sativa L.) and its effect on plant growth and farming cost efficiency. The research method used a Completely Randomized Design (CRD) with four treatments: P0 (100% rockwool as growing medium), P1 (50% rockwool + 50% lettuce root waste), P2 (50% lettuce root waste + 50% rockwool), and P3 (100% lettuce root waste). Observed variables included plant height, leaf area, fresh weight, and business feasibility analysis (R/C ratio, B/C ratio, ROI, and payback period). Results showed that P3 produced the highest growth in leaf area (78.12 cm²) and fresh weight (133 g), along with a 7% reduction in variable costs compared to P0. Financial analysis indicated an R/C ratio of 2.48 and ROI of 33%, demonstrating business feasibility. In conclusion, lettuce root waste is a viable alternative growing medium that enhances productivity and farming cost efficiency. Further research is recommended to test this innovation on other crops and promote its adoption among hydroponic farmers.